SINGLE-CRYSTAL ELASTICITY OF β-MG2SIO4 TO THE PRESSURE OF THE 410 KM SEISMIC DISCONTINUITY IN THE EARTHS MANTLE - Zha C.S.; Mao H.K.; Hemley R.J.; Duffy T.S.; Downs R.T.; Weidner D.J. (My University, 1997)
The complete set of elastic stiffness coefficients of a single crystal of Mg2SiO4 in the modified spinel (wadsleyite) structure are reported at eight pressures from ambient to 14 Gigapascals (GPa). All moduli vary linearly with pressure within the resolution of the data. Third-order Birch-Murnaghan equation fits to aggregate elastic moduli yield values of 170 (±2) GPa and 4.3 (±0.2) for the adiabatic bulk modulus and its first pressure derivative, and 115 (±2) GPa and 1.4 (±0.2) for the shear modulus and its pressure derivative. These data, together with previous results for α-Mg2SiO4, enable us to make the first in situ determination of the velocity increase due to the α-β transition at the pressure (~ 13.8 GPa) of the 410 km discontinuity. The room-temperature velocity increase at the transition pressure is 9.8% for compressional waves and 12.4% for shear waves.